1995
DOI: 10.1111/j.1432-1033.1995.0405e.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability, Activity and Structure of Adenylate Kinase Mutants

Abstract: Sequence/structure relationships have been explored by site-directed mutagenesis using a structurally known adenylate kinase. In particular the effects of helix capping and nonpolar core expansion on thermodynamic stability have been analyzed. Six point mutations were produced and characterized by SDS/ PAGE, native PAGE, isoelectric focussing, electrophoretic titration, enzyme kinetics, and X-ray structure analysis. Heat-denaturation experiments yielded melting temperatures T,,, and melting enthalpy changes AH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…However, the substitutions in the study were in the S2 subunit of the S protein and not near the furin cleavage site. The standard folding enthalpy measured at the melting temperature was higher for G614 S protein at 62.6 kcal/mol compared with 60.9 kcal/mol for D614 S protein, indicating that G614 S protein is less stable at 25 C (Spuergin et al, 1995). Substitutions can have either a stabilizing or a destabilizing effect on WT protein folding, whereby folding free energy measurements on RNA viral proteins with high substitution rates have demonstrated less stable protein structures (Wylie and Shakhnovich, 2011).…”
Section: S Protein D614g Substitutionmentioning
confidence: 99%
“…However, the substitutions in the study were in the S2 subunit of the S protein and not near the furin cleavage site. The standard folding enthalpy measured at the melting temperature was higher for G614 S protein at 62.6 kcal/mol compared with 60.9 kcal/mol for D614 S protein, indicating that G614 S protein is less stable at 25 C (Spuergin et al, 1995). Substitutions can have either a stabilizing or a destabilizing effect on WT protein folding, whereby folding free energy measurements on RNA viral proteins with high substitution rates have demonstrated less stable protein structures (Wylie and Shakhnovich, 2011).…”
Section: S Protein D614g Substitutionmentioning
confidence: 99%
“…Therefore, all the relationships that Myers et al (1995) observed for DSASA estimated using the glycine-tripeptide model (Shrake and Rupley 1973;Rose et al 1985;Miller et al 1987;Lesser and Rose 1990) are also valid if the change in solvent-accessible surface area is calculated from the present molecular dynamics simulations. These equations can be used to quantify, for example, DSASA from Clarke and Fersht (1993); z Griko and Privalov (1994); aa Filimonov et al (1993); bb Munoz et al (1994); cc Ropson et al (1990); dd Covalt et al (2001); ee Makhatadze et al (1994); ff Dabora and Marqusee (1994); gg Ionescu et al (2000); hh Zhang et al (1993); ii Hu et al (1992); jj Spuergin et al (1995).…”
Section: Databasementioning
confidence: 99%
“…Regarding thermodynamic analysis of D614G mutation, S-glycoprotein stability was assessed and it was found that mutant G614 loop, compared with wild type (WT) D614 loop, was a slightly more dynamic structure, marked by relatively less thermal stability and higher vibrational entropy. In agreement with this notion, G614 was found to be less stable than D614 at 25°C, as inferred from standard folding enthalpy [10]. Next, the authors analyzed the interatomic interactions in the G614 mutant S-glycoprotein and showed that the short 2.7-Å H-bond that existed between S1 (Chain A) and S2 (Chain B) side chains in the WT D614 was lost in the mutant G614 S-glycoprotein.…”
Section: Recapitulating the Main Findingsmentioning
confidence: 72%